Tshwane in transition : establishing an integrated tourism gateway to the capital - Akoob, Ahmed (My University, 2014)
The City of Tshwane is currently facing many challenges in terms of economic development. It continues to underperform when compared to other local cities. As a capital city, it’s meant to be the heart of a thriving government system but this is seen as absent to many. In order to combat the above, a framework has been put into place by the City. It sets out spatial and sectoral strategies for interventions that will diversify, repopulate and regenerate the inner city. Within this framework, tourism has been identified as a component that could play a vital role towards achieving the above. The tourism sector within Tshwane has the potential to thrive and contribute substantially to the city’s economy. Reasons for this large gap between the tourist offer and the tourist demand may be as a result of a lack of marketing and good infrastructure around the various tourist attractions. All of the notable tourist attractions require a driving force behind them that spurs on a greater demand for such an outstanding offer. Apart from this, the city must be marketed as an urban tourist destination. Urban tourism, for many, may be seen as an intangible incident. This is due to its abstract nature - cities are not built specifically for the pleasure seeking tourist. Urban tourism does, however, exist as a component of the city’s functioning. It finds itself intertwined with the day to day activities of the city. Services and facilities available do not make a distinction between residents and tourists. Being a capital city, Tshwane’s identity is meant to be synonymous with government presence. However, many problems are faced in this regard such as government departments shunning itself away from the public behind high fences. By further establishing the city’s identity as a centre of government activity, visitor numbers to the city can increase. The presence of government must not remain inaccessible to the public. Rather, through architecture we can create a system of noticeable government whereby government officials, residents and tourists begin to share common platforms of interaction. Our buildings must stand as symbolic signs of a thriving and open government in a democratic society. They must become representations of the city’s contemporary identity - an identity that is composed of a multitude of cultures, races and social classes. Ultimately, the urban environment shaped through government presence must become a must-see destination for the urban tourist. With the above in mind, a catalyst can be formulated that seeks to drive a greater demand for tourism in the area. At the same time, a stronger and more noticeable government presence can be formulated. Eventually, the city’s goals of urban, economic and social regeneration can be achieved.
Keywords: City planning--South Africa.; City planning--South Africa--City of Tshwane.; Urban renewal--South Africa.